Las falacias en las teorías contemporáneas de la argumentación - Claudio Fuentes Bravo; Cristián Santibáñez Yáñez (Logos: Revista de Lingüística, Literatura y Filosofía, 2017)
In this paper we use Hansson’s concept of formalized philosophy and the linked categories of simplified idealization and perfectionist idealization, aiming to metaanalyze three theoretical approaches to human argumentation: van Eemeren and Grootendorst’s pragmadialectics, Walton’s argumentative schemes, and Jacobs and Jackson’s conversational angle, in relation to their treatment of fallacies as a type of transgression of pragmatics rules. We conclude that while the two first theories are anchored in a centralized conception of the fallacious, the third theory abandons any possibility of normativity.